Endoplasmic reticulum pathology and stress response in neurons precede programmed necrosis after neonatal hypoxia‐ischemia. Issue 48 (28th November 2015) - Chavez‐Valdez, Raul; Flock, Debbie L.; Martin, Lee J.; Northington, Frances J.
Abstract: The endoplasmic reticulum (ER) is tasked, among many other functions, with preventing excitotoxicity from killing neurons following neonatal hypoxia‐ischemia (HI). With the search for delayed therapies to treat neonatal HI, the study of delayed ER responses becomes relevant. We hypothesized that ER stress is a prominent feature of delayed neuronal death via programmed necrosis after neonatal HI. Since necrostatin‐1 (Nec‐1), an inhibitor of programmed necrosis, provides delayed neuroprotection against neonatal HI in male mice, Nec‐1 is an ideal tool to study delayed ER responses. C57B6 male mice were exposed to right carotid ligation followed by exposure to FiO2 = 0.08 for 45 min at p7. Mice were treated with vehicle or Nec‐1 (0.1 μl of 8 μmol) intracerebroventricularly with age‐matched littermates as controls. Biochemistry assays at 3 and 24 h and electron microscopy (EM) and immunohistochemistry at 96 h after HI were performed. EM showed ER dilation and mitochondrial swelling as apparent early changes in neurons. With advanced neurodegeneration, large cytoplasmic fragments containing dilated ER "shed" into the surrounding neuropil and calreticulin immunoreactivity was lost concurrent with nuclear features suggestive of programmed necrosis. Nec‐1 attenuated biochemical markers of ER stress after neonatal HI, including PERK and eIF2α phosphorylation, and unconventional XBP‐1 splicing, consistent with the mitigation of later ER pathology. ER pathology may be an indicator of severity of neuronal injury and potential for recovery characterized by cytoplasmic shedding, distinct from apoptotic blebbing, that we term neuronal macrozeiosis. Therapies to attenuate ER stress applied at delayed stages may rescue stressed neurons after neonatal HI.